Study on Mapping the Market Potential and Accelerating Finance for Women Entrepreneurs in Bangladesh - Singh, Sanjana (International Finance Corporation, Washington, D.C., 2017)
International Finance Corporation (IFC) conducted a survey to identify opportunities and provide recommendations for facilitating finance for women small and medium enterprise (SME) entrepreneurs. Various stakeholders were interviewed during the survey which included 500 women SME entrepreneurs, women centric business associations, relevant government organizations as well as other associated institutions. Given the lack of gender based assessments in access to credit for women SME entrepreneurs in Bangladesh, the survey report aimed at identifying the potential opportunities for facilitating finance to these entrepreneurs. This also involved developing comprehensive knowledge of the environment that women entrepreneurs operate in and in estimating their current financing gap. Alongside this, the study sought to highlight the major challenges faced by these entrepreneurs that prevent a satisfactory uptake of loan products.